Effects of Wind-Hardened Snow on Foraging by Reindeer (Rangifer Tarandus) - Collins, W.B.; Smith, T.S. (ARCTIC, 1991)
Various methods were investigated for assessing the relationship between wind-hardened snow (upsik) and forage availability to reindeer. Mean bottom area of individual craters was not a function of depth, hardness or integrated hardness. Individual crater area was partially dependent on specific cratering time (r2 = .60). Cratering time per active period increased with integrated snow hardness (r2 = .88). Number of craters and total area cratered increased with decreasing site hardness. Reindeer always cratered microsites of lesser depth and hardness than found in the general feeding site. A threefold decrease in snow hardness resulted in a fourfold increase in forage availability.Key words: Rangifer, snow hardness, snow depth, forage availability Mots clés: Rangifer, dureté de la neige, profondeur de la neige, accessibilité aux plantes fourragères